Estimation of the current healthcare costs of gout in Liaoning Province from 2015 to 2022 based on the SHA2011 accounting system - Shi, Xiaoxia; Zheng, Fengchun; Wan, Quan; Chai, Peipei; Wang, Guilin; Pang, Zhenmiao; Ma, Yuedan (Frontiers in Public Health, 2025)
BackgroundGout has become a major public health problem worldwide, causing severe pain, discomfort, inflammation, mobility problems and impaired physical functioning, resulting in heavy economic losses and social burdens.MethodsThe study was based on System of Health Accounts 2011 (SHA2011) and data of 97,907 patients from 1,084 healthcare organizations were taken using multistage stratified random sampling method. Descriptive analysis of therapeutic care expenditures (CCE), Sankey diagram to analyze the flow of CCE, Mann–Whitney U test to analyze 2 independent samples, Kruskal-Wallis H to analyze K independent samples significance. Multifactorial analysis of CCE influences, Structural Equation Modeling (SEM) to analyze the direct and indirect effects and mediating role.ResultsCCE increases from CNY 25.32 million in 2015 to CNY 116.02 million in 2022, with a concentration of ages 30–69. The proportion of public health financing decreases with age and is dominated by general hospitals. The difference is significant in single-factor analysis, and the high cost in multi-factor analysis is related to purchase drugs, elective treatment, basic medical insurance for urban and rural residents, provincial level, Chinese medicine hospitals, and large standardized coefficients in 2020, and outpatient/inpatient care, drugs, type of institution, insurance status, and gender by path coefficients in the SEM in the order of directly or indirectly affecting the CCE.ConclusionGout disease in Liaoning Province imposes a heavy financial burden on patients and the health insurance system. It is recommended to increase reimbursement for gout inpatient costs, improve primary care guidelines and purinol dose adherence, strengthen primary care collaborative personalized education and care to achieve uric acid-lowering effects, increase subsidies and inclusion of gout prescription medications in the local health insurance directory, and for men to reduce consumption of high-purine foods and alcohol at social events.